2019
DOI: 10.1136/bmjopen-2019-031892
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for patients with cancer-induced xerostomia: a systematic review protocol

Abstract: IntroductionXerostomia is a common symptom in patients with cancer. Currently available methods to manage xerostomia include stringent oral hygiene using fluoride agents and antimicrobials, saliva substitutes and sialagogic agents, but side effects such as headache, dizziness and sweating can occur with these therapies. Clinical trials have shown that acupuncture may be effective in treating xerostomia. The objective of this systematic review is to assess the effectiveness and safety of acupuncture treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, another study revealed that acupuncture can alleviate dry mouth symptoms in some patients after radiation therapy by stimulating the residual salivary gland tissue. Blom et al reported a noteworthy increase in unstimulated and stimulated salivary flow rates in individuals with xerostomia of different origins, including radiation therapy, after receiving 24 acupuncture treatments [92][93][94]. Further research is required to ascertain the comparative effectiveness and replicability of the outcomes [92][93][94].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study revealed that acupuncture can alleviate dry mouth symptoms in some patients after radiation therapy by stimulating the residual salivary gland tissue. Blom et al reported a noteworthy increase in unstimulated and stimulated salivary flow rates in individuals with xerostomia of different origins, including radiation therapy, after receiving 24 acupuncture treatments [92][93][94]. Further research is required to ascertain the comparative effectiveness and replicability of the outcomes [92][93][94].…”
Section: Managementmentioning
confidence: 99%
“…Blom et al reported a noteworthy increase in unstimulated and stimulated salivary flow rates in individuals with xerostomia of different origins, including radiation therapy, after receiving 24 acupuncture treatments [92][93][94]. Further research is required to ascertain the comparative effectiveness and replicability of the outcomes [92][93][94].…”
Section: Managementmentioning
confidence: 99%
“…Herbal medicines were also found to enhance salivary function and to decrease the severity of mouth dryness in cancer patients [119]. In spite of several RCTs of acupuncture as a management for dry mouth have been stated to date, its cumulative evidence for its effectiveness has not been systematically estimatted [120]. An organic thiophosphate is amifostine that can protect cells from radiation distruction by scavenging oxygen-derived free radicals.…”
Section: Xerostomia Prevention Therapiesmentioning
confidence: 99%